Association of trimethylamine N-oxide with coronary atherosclerotic burden in patients with non-ST-segment elevation myocardial infarction. Issue 27 (2nd July 2020) - Bin Waleed, Khalid; Lu, Yongkang; Liu, Qiang; Zeng, Fanfang; Tu, Hong; Wei, Yi; Xu, Shuai; Zhang, Zhiling; Rongfeng, Yang; Fan, Ailing; Altaf, Afrasyab; Chang, Junlei; et al.
Abstract: Background: Recently, trimethylamine N-oxide (TMAO) unexplained gut microbe has been proposed as a promising risk factor for atherosclerotic cardiovascular disease (CVD) pathogenesis and adverse events. The relationship of TMAO with coronary atherosclerotic burden has been evaluated in patients with stable coronary artery disease and ST-segment elevation myocardial infarction, but still needs to be explored in newly diagnosed non-ST-segment elevation myocardial infarction (NSTEMI) patients. Material and methods: A prospective, single-center, SZ-NSTEMI trial (ChiCTR1900022366) is underway to investigate the relationship of TMAO with the severity and prognosis of coronary atherosclerosis in newly diagnosed NSTEMI patients who will undergo coronary angiography with primary percutaneous coronary intervention (pPCI). The primary endpoint of the study will be assessed the association of TMAO with coronary atherosclerotic severity quantify by the number of diseased coronary arteries and SYNTAX score after the coronary angiography. The secondary endpoints will be identified the TMAO as a prognostic biomarker for the short (1 month) and long-term (12 months) major cardiovascular and cerebrovascular events (MACCEs) rate including myocardial infarction, target vessel revascularization, stroke, heart failure, all-cause rehospitalization, and all-cause mortality after the pPCI. The blood samples will be collected from each patient before the procedure to measure the TMAO by isotope dilution high-performance liquid chromatography. In conclusion, SZ-NSTEMI will be the first cohort that will be investigated the association of TMAO with the severity and prognosis of coronary atherosclerotic burden in NSTEMI patients, aiming to identify TMAO as a predictor and a prognostic biomarker.